Tributyl phosphate modified biochar activated PMS for degradation of bisphenol A - FU Xiangyu; LI Yafeng; LIU Yihan; CUI Keqing; WANG Lingping (Gongye shui chuli)
Using bisphenol A(BPA) as the target pollutant, phosphorus-doped biochar(P-bio) was prepared by impregnation pyrolysis with corn stover and tributyl phosphate as the raw materials. The structure of P-bio was characterized and analyzed, and the effects of persulfate(PMS) concentration, P-bio dosage, and initial pH on BPA degradation by P-bio activated PMS system were further explored. The results indicated that the surface of P-bio was a sheet-like structure composed of obvious folds, which was porous and loose. The specific surface area of P-bio was 173.985 m²/g, which was 93.4 times higher than that of pure biochar(1.863 m²/g). Under the conditions of BPA concentration of 10 mg/L, P-bio dosage of 2 g/L, pH of 3.21, and PMS dosage of 2 mmol/L, the removal rate of BPA by P-bio activated PMS system was 99.47% after 30 minutes, and the reaction rate constant was 0.164 3 min-1. It was further confirmed by EPR quenching that active radicals SO4·- and ·OH were generated in the P-bio activated PMS system, which contributed to the degradation of BPA by 12.07% and 87.93%, respectively. For the reuse of P-bio, BPA removal rate was 74.1% at the 2nd use and 68% at the 3rd use, and BPA removal rate recovered to 80.7% after calcination of P-bio after three consecutive uses, which indicated that the P-bio catalyst had strong reusability and regeneration performance.